Mutu Mikrobiologis dan Organoleptik Ikan Cakalang (Katsuwonus pelamis L) Segar di Palka Kapal Ikan PPP Tumumpa - Dara Enjelia Sahambangun; Henny Adeleida Dien; Nurmeilita Taher; Joyce C. V. Palenewen; Djuhria Wonggo; Daisy Monica Makapedua (Sam Ratulangi University, 2022)
Skipjack (Katsuwonus pelamis L) is a most popular product for the people of North Sulawesi. As a perishable foodstuff, fish requires special treatment to maintain their quality. Deterioration of quality in fish can cause diseases for those who consume. This research was conducted to analyze the quality of microbiological and organoleptic of skipjack tuna. The research method used is quantitative descriptive, with test parameters was total plate count (TPC), total Coliforms and Escherichia coli, Organoleptic (eyes, gills, flesh mucus, odor, texture) and pH. Samples were taken at two ship hatch. The test results of fresh skipjack tuna showed that the highest TPC value of fresh skipjack tuna was 2.8x103cfu/g on the 3rd take in ship hatch 2 and the lowest TPC value of 1.5x103cfu/g on the 1st take in ship hatch 2. The highest TPC value in the water sample used is 3.2x103 in the 1st pick-up in ship hatch 2, and the lowest TPC value is 2.6x103cfu/g at the second take-up in ship hatch 2. The results of the analysis of total Coliforms and E. coli showed positive results in ship hatch 1 and ship hatch 2. Based on the organoleptic analysis of fresh skipjack tuna in hatch 1 and hatch 2, it shows a value of 8–7 which means the fish is still fresh. The pH value of fresh skipjack tuna is 5.8–5.85 and the water samples used are 7.2–7.4 indicating that the fresh skipjack fish and the water used in hatches 1 and 2 are still in good condition (fresh).Keyword: Escherichia coli, pH, Organoleptic, pH, Skipjack tuna, Total Plate Count. Ikan Cakalang (Katsuwonus pelamis L) merupakan produk primadona bagi masyarakat Sulawesi Utara. Ikan memerlukan penanganan yang cepat, cermat dan tepat supaya kualitasnya tetap baik. Penelitian ini dilakukan untuk menganalisis mutu mikrobiologis dan organoleptik dari ikan cakalang segar. Metode penelitian yang digunakan yaitu deskriptif kuantitatif, dengan parameter uji yakni angka lempeng total (ALT), total Koliform dan Escherichia coli, organoleptik (mata, insang, daging, lendir, bau dan tekstur) dan pH. Sampel ikan cakalang segar dan air diambil pada dua palka kapal ikan. Hasil pengujian ikan cakalang segar menunjukkan nilai ALT tertinggi ikan cakalang segar yaitu 2,8x103cfu/g pada pengambilan ketiga di palka 2 dan nilai ALT terendah yaitu 1,5x103cfu/g pada pengambilan pertama di palka 2. Nilai ALT tertinggi pada sampel air yaitu 3,2x103 cfu/g pada pengambilan pertama di palka 2, dan nilai ALT terendah yaitu 2,6x103cfu/g pada pengambilan kedua di palka 2. Hasil analisis total koliform dan Escherichia coli menunjukkan hasil positif di palka 1 dan palka 2. Hasil analisis organoleptik ikan cakalang segar di palka 1 dan palka 2 menunjukkan nilai 8–7 yang berarti ikan masih dalam keadaan segar. Nilai pH ikan cakalang segar yaitu 5,8–5,9 dan sampel air yang digunakan yaitu 7,2–7,4 menunjukkan bahwa ikan cakalang segar dan air yang digunakan di palka 1 dan palka 2 masih dalam keadaan baik (segar).Kata kunci: Cakalang, Escherichia coli, Organoleptik, pH, Angka Lempeng Total.